Denitrification and environmental factors influencing nitrate removal in Guaymas Basin hydrothermally altered sediments - Bowles, Marshall W.; Nigro, Lisa M.; Teske, Andreas P.; Joye, Samantha (Frontiers in Microbiology, 2012)
We measured potential nitrate removal and denitrification rates in hydrothermally altered sediments inhabited by Beggiatoa mats and adjacent brown oil stained sediments from the Guaymas Basin, Gulf of California. Sediments with Beggiatoa maintained slightly higher rates of potential denitrification than did brown sediments at 31.2 (±12.1) versus 21.9 (±1.4) μM N d-1, respectively. In contrast, the nitrate removal rates in brown sediments were higher than those observed in mat-hosting sediments at 418 ± 145 versus 174 ± 74 μM N d-1, respectively. Additional experiments were conducted to assess the responses of denitrifying communities to environmental factors (i.e. nitrate, sulfide, and dissolved organic carbon (DOC) concentration). The denitrifying community had a high affinity for nitrate (Km = 137 ± 91 μΜ ΝΟ3-), in comparison to other environmental communities of denitrifiers, and were capable of high maximum rates of denitrification (vmax = 1164 ± 153 μM N d-1). The presence of sulfide resulted in significantly lower denitrification rates. Microorganisms with the potential to perform denitrification were assessed in these sediments using the bacterial16S rRNA gene and nitrous oxide reductase (nosZ) functional gene libraries. The bacterial 16S rRNA gene clone library was dominated by Epsilonproteobacteria (38%), some of which (e.g. Sulfurimonas sp.) have a potential for sulfide dependent denitrification. The nosZ clone library did not contain clones similar to pure culture denitrifiers; these clones were most closely associated with environmental clones.